(untitled) (Global Journal of Human-Social Science, 2024)
The National Social Assistance Policy in Brazil during the Bolsonaro (dis)government period is vehemently affected by its ultraneoliberal dynamics of underfunding and moralization. Therefore, the present work seeks to present some aspects about the defunding, implementation and effectiveness of this policy in this period. Our methodology encompasses bibliographical and documentary research of the exploratory type, using historical-dialectical materialism as a method. Therefore, we conclude that Bolsonaro fulfilled the objective he proposed when he became president of the republic of dismantling any type of social protection for the most vulnerable, like the National Social Assistance Policy itself, aggravating social inequalities.